A backup orientation system based on inverse problems technique - Nenarokomov, Aleksey V.; Chebakov, Evgeny V.; Krainova, Irina V.; Reviznikov, Dmitry L.; Morzhukhina, Alena V. (Computer Assisted Methods in Engineering and Science, 2019)
The correct orientation of the spacecraft during a space flight is one of the main tasks of astronautics, because its orientation affects the correct operation of all subsystems, in particular power supply systems, where the orientation of solar panels is one of the key tasks. From this point of view, the tasks of developing backup or replacement of orientation systems are becoming relevant. In this paper, an alternative for the development of an orientation sensor is proposed, which is sensitive to radiation heating from the Sun or other celestial bodies that emit strongly. Thus, the tasks of developing a heat flux sensor responsive to changes in heat fluxes become relevant. This article is devoted to the analysis of technical capabilities to create such a sensor.